2018
DOI: 10.1002/smll.201800634
|View full text |Cite
|
Sign up to set email alerts
|

Robust and Stable Cu Nanowire@Graphene Core–Shell Aerogels for Ultraeffective Electromagnetic Interference Shielding

Abstract: Cu nanowires (CuNWs) are considered as a promising candidate to develop high performance metal aerogels, yet the construction of robust and stable 3D porous structures remains challenging which severely limits their practical applications. Here, graphene-hybridized CuNW (CuNW@G) core-shell aerogels are fabricated by introducing a conformal polymeric coating and in situ transforming it into multilayered graphene seamlessly wrapped around individual CuNWs through a mild thermal annealing process. The existence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
81
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(81 citation statements)
references
References 40 publications
0
81
0
Order By: Relevance
“…Thus, the compressibility of CPCs should be rstly considered when one wants to obtain high-efficiency EMI shielding ability. Encouragingly, there are several publications about compressive behavior of EMI shielding materials under force stimulation, such as carbon-wrapped metallic Ag nanowire hybrid sponges, 16 Cu nanowire@graphene core-shell aerogels, 17 porous multiwalled carbon nanotube/water-borne polyurethane composites, 18 light graphene foams, 19,20 and carbon nanotube-multilayered graphene edge plane core-shell hybrid foams. 21 These materials exhibited exceptional EMI shielding properties along with superior compressibility, which renders their great potential as promising candidates for highperformance EMI shielding in exible electronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the compressibility of CPCs should be rstly considered when one wants to obtain high-efficiency EMI shielding ability. Encouragingly, there are several publications about compressive behavior of EMI shielding materials under force stimulation, such as carbon-wrapped metallic Ag nanowire hybrid sponges, 16 Cu nanowire@graphene core-shell aerogels, 17 porous multiwalled carbon nanotube/water-borne polyurethane composites, 18 light graphene foams, 19,20 and carbon nanotube-multilayered graphene edge plane core-shell hybrid foams. 21 These materials exhibited exceptional EMI shielding properties along with superior compressibility, which renders their great potential as promising candidates for highperformance EMI shielding in exible electronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…65‐2869) and Cu (JCPDS Card No. 04‐0836) . Energy dispersive X‐ray spectroscopy (EDS) mappings (Figure S2, Supporting Information) indicated that Cu and Al distributed homogenously in this nanocomposite film.…”
Section: Methodsmentioning
confidence: 98%
“…Recently, the resilience of lightweight porous materials has received enormous attention in some emerging materials, like graphene aerogel or nanosponges, [17] carbon nanotubes aerogel, [18] nanofiber-based aerogel, [19] metallic nanowires aerosponges. [20] Attributed to high pressure-sensitivity and good resilience, those materials could be applied to ultrasensitive sensors, [21] reusable pollutant absorbers, [22] high-efficiency mechanical damper, [23] or adjustable microwave inhibitor. [24,25] Apparently, the resilience of the sponge has been an important factor for expanding the functionalities of materials, enhancing the performance of components and prolonging the service lifetime of devices.…”
Section: Introductionmentioning
confidence: 99%
“…However, although porous metallic sponges have been studied for many years, little attention was paid to the research about the resilience of metallic sponges attributed to the inherent plastic nature of metal. Recently, the resilience of lightweight porous materials has received enormous attention in some emerging materials, like graphene aerogel or nanosponges, carbon nanotubes aerogel, nanofiber‐based aerogel, metallic nanowires aerosponges . Attributed to high pressure‐sensitivity and good resilience, those materials could be applied to ultrasensitive sensors, reusable pollutant absorbers, high‐efficiency mechanical damper, or adjustable microwave inhibitor .…”
Section: Introductionmentioning
confidence: 99%